Internalization of tolerance value in thematic learning at Madrasah Ibtidaiyah - Luma'ul 'Adilah Hayya; Fauzi Fauzi; Handini Nindya Anggita; Ahmad Bagus Romadhon; Akmalia Umami Al Fatah (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2023)
Character education, according to Lickona, is a conscious attempt to assist someone in understanding, paying attention to, and carrying out essential ethical values. The Indonesian Ministry of National Education has established eighteen values for character education, one of which is tolerance. At the age of Madrasah Ibtidaiyah, intelligence tolerance must be instilled. Almost all elementary schools apply thematic learning models, which encourage students to actively explore and discover scientific concepts and principles meaningfully. This study aims to analyze how to plan, implement, and assess the value of tolerance in thematic learning at elementary schools. The author is interested in researching the internalization model of tolerance values in thematic education conducted at MIN 3 Purbalingga, Indonesia. Researchers use a type of field research of a qualitative descriptive method based on the philosophy of post-positivism. The sampling technique was used as a source of information using purposive and snowball techniques. Observation, interviews, and documentation techniques were employed to collect data. There were three phases to the data analysis: reduction, data presentation, and conclusion. The results of the data analysis in the preparation stage for class teachers have developed a syllabus and lesson plans, but they do not include tolerance values. The implementation of learning the importance of tolerance to students is carried out by linking material to learning themes following the deal of patience. No specific format is specified in the lesson plan for the assessment process; the teacher evaluates by directly observing student activities and is regarded spontaneous during the learning process.